A catalytic reaction-based colorimetric assay of alkaline phosphatase activity based on oxidase-like MnO2 microspheres. Issue 42 (18th October 2019) - Wang, Linjie; Ye, Kun; Pan, Jianming; Song, Hongwei; Li, Xin; Niu, Xiangheng
Abstract : A catalytic reaction-based colorimetric assay of alkaline phosphatase activity is developed based on oxidase-like MnO2 microspheres. Abstract : As a typical biomarker for disease diagnosis in clinical practice, alkaline phosphatase (ALP) plays a critical role in regulating the dephosphorylation process of biomolecules. On this account, exploration of an effective and simple means of ALP activity measurement becomes very significant. In this work, we report a catalytic reaction-based colorimetric method for the monitoring of ALP activity via employing nanostructured MnO2 as a favorable oxidase mimic. The prepared MnO2 microspheres exhibit good oxidase-like capacity to induce the catalytic oxidation of colorless 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to deep-blue TMBox; when ALP hydrolyzes ascorbic acid phosphate, the produced ascorbic acid (AA) with a certain reducing power can destroy the MnO2 enzyme mimic by reducing it to Mn 2+, dramatically suppressing the TMB chromogenic reaction. Based on the strategy, a convenient and high-performance colorimetric method was established for ALP activity sensing, giving a wide linear range from 0.5 to 120 U L −1 . With the help of N -ethylmaleimide as an efficient masking agent for biothiols, the colorimetric approach could provide excellent specificity for ALP activity detection. Reliable and precise measurement of the analyte in practical samples was also verified by our assay, indicating its promise as a feasible tool for clinical diagnosis.